Pendidikan Kesehatan Manajemen Stres menggunakan Terapi Hipnosis Lima Jari pada Remaja di Desa Rancamulya dan Desa Kedokan Gabus - Carsita, Wenny Nugrahati; Windiramadhan, Alvian Pristy; Mujahidah, Rd. Gita; Husnaniyah, Dedeh; Riyanto, Riyanto (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2024)
Background: Adolescence is a transitional period from childhood to adulthood where physical, cognitive, and emotional changes occur. Changes in adolescents trigger stress. The impact of unresolved stress can trigger maladaptive behavior, disrupt physical, psychological health, and disrupt the stages of development in adolescents. One of the stress management is the five-finger hypnosis therapy. Purpose: Community service activities aim to increase adolescents' knowledge about stress management using five-finger hypnosis therapy. Methods: The method of implementation with lectures and questions and answers. The activity was carried out for 1 day at the Rancamulya and Kedokan Gabus village, Gabus Wetan District, Indramayu Regency. Activity procedures include pre-test, health education and post-test. The targets of this activity were 33 adolescents. Results: There is an increase in knowledge in adolescents before and after the activity with an average score before being given health education of 76 and after being given material of 88. Conclusion: After health education for adolescents, adolescents' knowledge about stress management using five-finger hypnosis therapy increased. It is expected that community service activities will be performed regularly so that adolescents can manage stress.